2011
DOI: 10.1111/j.1468-1331.2010.03144.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficient recognition of emotional prosody in primary focal dystonia

Abstract: Together these findings bring further insight into the basal ganglia involvement in processing of emotional prosody and emphasize the importance to identify the psychopathological symptoms in patients with CD as complementary to the motor deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
2
22
1
1
Order By: Relevance
“…Which are the relations between prosody and motor control at neuroanatomical level? Data obtained from patients with primary focal dystonia evidenced a significant impairment in auditory prosody recognition compared to an healthy population ( Nikolova et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Which are the relations between prosody and motor control at neuroanatomical level? Data obtained from patients with primary focal dystonia evidenced a significant impairment in auditory prosody recognition compared to an healthy population ( Nikolova et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 32 patients (20 with cervical dystonia and 12 with blepharospasm) found that patients had difficulty identifying the facial expression of “disgust” compared to age‐matched controls, with nonsignificant trends for impaired recognition of happiness and sadness . Another study of the perception of emotional speech prosody reported deficits in the recognition of angrily intonated words in 30 patients with cervical dystonia, compared to control participants …”
Section: The Psychiatry Of Cervical Dystonia and Disordered Social Comentioning
confidence: 99%
“…Among these, most crucial is the fundamental frequency (F0), followed by duration, and intensity [2]. A great deal of work in neuropsychology has focused on emotional prosody in normal-hearing (NH) individuals and in neurological conditions such as Parkinson’s disease [3] and primary focal Dystonia [4] but rarely in individuals with hearing loss. Individuals with severe to profound hearing loss have a limited dynamic range of frequency, temporal and intensity resolution, thus impairing their perception of prosody.…”
Section: Introductionmentioning
confidence: 99%